Advances in mergers and acquisitions - Cooper, Cary L.; Finkelstein, Sydney (Emerald Publishing Limited, 2017)
Advances in Mergers and Acquisitions stands out from the competition due to its focus on three key characteristics: studies from scholars in different countries, with different research questions, relying on different theoretical perspectives. Such a broad and inclusive approach to mergers and acquisitions is not easily replicated in academic journals, with much narrower mandates and metrics. The chapters published in this volume provide cutting edge ideas by leading scholars, and help to inform mergers and acquisitions research around the world.
Prelims -- Alliances to acquisitions: a road map to advance the field of strategic management -- Pre-M&A "Leadership": Might behavioral due diligence assessment be the answer? -- The decision to retain and reduce human resources in mergers and acquisitions -- Strategic investment appraisal: multidisciplinary perspectives -- Can SPACs ensure M&A success? -- Mergers and acquisitions revisited: the role of business model relatedness -- Training during transitions: the context of a developing economy -- Dissecting post-merger integration risk: the PMI Risk framework -- Getting beyond culture clashes: a process model of post-merger order negotiation -- A stakeholder framework for evaluating the impact of mergers and acquisitions -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Consolidation and merger of corporations; Business & Economics -- Mergers & Acquisitions; Takeovers, mergers & buy-outs.